2005
DOI: 10.1007/s00421-005-1400-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fatiguing protocol on motor imagery accuracy

Abstract: This study was devised to evaluate the influence of muscle fatigue on athletes' ability to perform motor imagery. Performance impairment is a consequence of fatigue, but alterations on perception and mental activity may also occur. To test whether peripheral fatigue affects mental processes, ten sports students imagined three consecutive countermovement jumps before and after a fatiguing protocol, through repetition of upright movements, at 70% of maximal voluntary contraction, until exhaustion. Autonomic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Mental fatigue alters motor performance. Specifically, high-load mental cognitive tasks (e.g., incongruent Stroop task) for about 20min altered maximal force production of elbow flexor [38], and task-induced mental fatigue altered the speed accuracy of actual performance and MI [39]. Furthermore, repetitive MI led to participants having difficulties in maintaining focused attention on imagined movement.…”
Section: Discussionmentioning
confidence: 99%
“…Mental fatigue alters motor performance. Specifically, high-load mental cognitive tasks (e.g., incongruent Stroop task) for about 20min altered maximal force production of elbow flexor [38], and task-induced mental fatigue altered the speed accuracy of actual performance and MI [39]. Furthermore, repetitive MI led to participants having difficulties in maintaining focused attention on imagined movement.…”
Section: Discussionmentioning
confidence: 99%
“…They certainly call for a closer examination in light of the fundamentally strong relation usually found between actual and mental durations, and the fact that effort and physiological conditions appear to be well represented in MI (Courtine et al 2004;Decety et al 1993;Guillot et al 2005). In this context, a study relying on different load conditions showed a dissociation between actual and imagery durations and disproportionately long mental durations only for heavier loads (Slifkin 2008).…”
Section: Introductionmentioning
confidence: 90%
“…For example, heart rate and pulmonary frequencies are known to covary with the degree of imagined effort [Decety et al, 1991[Decety et al, , 1993Fusi et al, 2005]. Furthermore, increases in ventilation and systolic blood pressure have also been reported during MI of dumbbells lifting [Wang and Morgan, 1992;Wuyam et al, 1995], whereas similar electrodermal and thermovascular responses have been elicited during MI and motor performance [Guillot et al, 2004[Guillot et al, , 2005. Finally, the advent of brain mapping techniques like positon emission tomography and functional magnetic resonance imaging (fMRI) have shown that goaldirected actions, whether executed or imagined recruit similar (albeit non identical) neural substrates [Decety et al, 1994;Lotze et al, 1999;Mellet et al, 1998].…”
Section: Introductionmentioning
confidence: 90%